Evaluation of Health-related Quality of Life in Regular Hemodialysis Patients Using the KDQOL-SFTM Questionnaire - Eliseo Capote Leyva; Raydel Argudín Selier; Salvador Roberto Mora González; Lázaro Capote Pereira; Idrissa Leonard Rupalé; Yosvany Moret Hernández (Medisur)
Background: in end-stage chronic renal failure, treatments like hemodialysis induce substantial changes in lifestyle. Such therapies aim to achieve functional improvement by reducing symptoms and/or slowing disease progression. Objective: to evaluate the health-related quality of life in patients undergoing regular hemodialysis. Methods: a cross-sectional study was conducted in chronic renal failure patients undergoing regular hemodialysis in the hemodialysis and peritoneal dialysis service of the Dr. Carlos J. Finlay Military Hospital from January through February 2013. The Kidney Disease Quality of Life Short Form version 1.3 was used to evaluate the health-related quality of life. Results: generic dimensions with lower scores were the physical role, general health perception and emotional role. The specific dimensions with lower scores were the burden of kidney disease, employment status and sexual function while dimensions with higher scores were specific: relationship with the dialysis staff (85.62 points), cognitive function (84.33 points) and quality of social relationship (82.88 points). Conclusion: As in other countries, the KDQOL-SF enables the evaluation of health-related quality of life in regular hemodialysis patients in Cuba, since it allows effectively identifying the dimensions and areas most affected.